Trening koordynacyjny w grach sportowych. Wybrane podstawy teoretyczno-metodyczne - Liakh, V. (Human Movement, 2001)
In the paper an attempt was made of justifying the concept of coordination developing in sport. Aspects of planning, different variants of training of coordination motor abilities (CMA), coordination complexity, loads selection, as well as rest intervals in CMA-training were analysed. Also, analysis of training plans for beginning and advanced basketball, handball and soccer players was carried out. The answers to the questions under consideration were also searched for on the basis of available literature analysis. On the basis of the analysis carried out it turns out that there are 5 concepts of coordination developing in sport. The author is in favour of a concept which says that coordination preparation in sport games has its own specific tasks, contents, volume and intensity. Taking into account the accomplished analysis, it has been announced that the time division into general and special coordinational preparation, in the light of different kinds of preparation in sport games, can look like time division in table 1. There were four effective variants of CMA-training distinguished. There were also established hypothetical proportions of exercises of various coordination complexity in many years' preparation of players in sport games (table 2).